Connecting chromosome replication with cell growth in bacteria. (December 2016) - Murray, Heath
Graphical abstract: Highlights: S. elongatus synthesizes DNA during lag phase before growth and division. Multiple regulatory systems coordinate DNA replication with cell growth in B. subtilis . The alarmone (p)ppGpp can target DNA replication initiation and elongation. Nutritional control of DnaA accumulation by regulated translation in C. crescentus . Abstract : For bacteria to proliferate they must duplicate their genetic material so that it can be passed to their progeny. This requires that DNA replication is coordinated with cell growth and division. In the natural environment bacterial growth is dynamic and strongly influenced by changes in nutrient availability. Recent studies have found that bacteria utilize a range of regulatory systems, many of them species-specific, to coordinate DNA replication with cell growth. This variability likely reflects the diverse lifestyles of different bacterial types.